Tesis de Maestría : algunos consejos prácticos - Ubertone, Fermín Pedro (2015)
This work is aimed at students who are currently completing a master's or doctoral thesis, or plan to begin one in the near future. On the basis of his personal experience in different roles related to the completion of a thesis, the autor provides some guidelines to help them achieve a better understanding of what needs to be done to write up the research. Also, he gives some practical advice that cannot be learned from books usually.